2023
DOI: 10.7717/peerj.14765
|View full text |Cite
|
Sign up to set email alerts
|

Acteoside alleviates UUO-induced inflammation and fibrosis by regulating the HMGN1/TLR4/TREM1 signaling pathway

Abstract: Purpose Acteoside (Act), a phenylethanoid compound that was first isolated from mullein, has been widely used for the investigation of anti-inflammatory and anti-fibrotic effect. However, the mechanism of Act against unilateral ureteral obstruction (UUO)-mediated renal injury is largely unknown. Therefore, this study aimed to explore the effects of Act on UUO rats and possible mechanisms. Methods A total of 20 Sprague-Dawley (SD) rats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…[102] After unilateral ureteral obstruction (UUO) in mice and rats, the expression of TREM-1 in the kidneys was upregulated. [48,[102][103][104] In a study, Tammaro et al [102] constructed a UUO model using TREM-1/3 KO mice and DPA12 KO mice, demonstrating that TREM-1 affects renal inflammation through the DAP12 pathway but does not affect fibrosis. A similar study showed that intraperitoneal injection of TREM-1-Fc had no significant effect on renal injury or fibrosis.…”
Section: Renal Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…[102] After unilateral ureteral obstruction (UUO) in mice and rats, the expression of TREM-1 in the kidneys was upregulated. [48,[102][103][104] In a study, Tammaro et al [102] constructed a UUO model using TREM-1/3 KO mice and DPA12 KO mice, demonstrating that TREM-1 affects renal inflammation through the DAP12 pathway but does not affect fibrosis. A similar study showed that intraperitoneal injection of TREM-1-Fc had no significant effect on renal injury or fibrosis.…”
Section: Renal Fibrosismentioning
confidence: 99%
“…This suggests that the HMGN1 protein may activate the TREM-1 signaling pathway by triggering the TLR4 protein, leading to inflammation fibrosis development in the kidney. [104] It is well known that macrophages play an important role in fibrosis. Lo et al [48] found that the expression level of the M1 marker in the kidneys of TREM-1 KO mice was significantly lower than that of control mice, while the expression level of the M2 marker was the opposite.…”
Section: Renal Fibrosismentioning
confidence: 99%
“…The unilateral ureteral obstruction (UUO) animal model of kidney injury has been widely used to investigate the mechanisms of kidney injury and the therapeutic values of numerous agents [ 83 , 84 , 85 , 86 , 87 ]. This model has certain advantages in that it is a nonuremic normotensive disorder in the absence of any apparent inflammatory or toxic insult to the kidneys [ 88 ].…”
Section: Protective Roles Of α-Lipoic Acid (Ala) In Kidney Injurymentioning
confidence: 99%
“…Previous reports have shown that TREM1 is upregulated in bleomycin-treated mouse alveolar epithelial cells, exerting pro-fibrotic effects in the lung by inducing cellular senescence [16]. Additionally, reducing TREM1 protein expression attenuates renal inflammation and fibrosis in rats subjected to unilateral ureteral obstruction [17]. The binding of soluble TREM1 to the membrane receptor ring guide receptor 2 activates downstream Smad2/3 and phosphatidylinositol-3-kinase (PI3K)/protein kinase B (Akt) signaling pathways, promoting hepatic stellate cell activation and liver fibrosis [18].…”
Section: Introductionmentioning
confidence: 99%